O incidente de resolução de demandas repetitivas-IRDR no microssistema dos juizados especiais federais: uma análise empírica sobre a (in)observância do art. 489, § 1º, V, do CPC/2015, nos acórdãos do STJ (2016-2019). - Pinho, Paulo Roberto Parca de (2021)
With the creation of the Repetitive Demand Resolution Incident - IRDR in Brazilian Civil Code of Procedure - CPC/2015 (article 976), an important debate arises about the application of the theses defined by the Federal Regional Courts within the scope of the Small Claims Courts at the federal level. The study intends to analyze the questions, from the dogmatic point of view, about the constitutionality, origin, legal nature and requirements for the establishment of the IRDR. In addition, it proposes to assess whether the legal thesis defined in the IRDR has been applied within the scope of the Small Claims Courts at the federal level, considering the express provision of articles 982, I and 985, I, CPC / 2015, based on the qualitative empirical analysis of judgments rendered within the scope of the Federal Regional Courts in the last 04 (four) years. It also aims to offer proposals to make the new incident compatible with the existence of its own uniform system provided for in article 14 of Law 10.259 / 01 (Law of the Small Claims Courts at the federal level), in order to ensure greater efficiency in the application of the new instrument for solving repetitive demands. From what can be seen, at the end of the study, the new technique has been used by most of the Federal Regional Courts and can give rationality and uniformity to the decisions in the Small Claims Courts at the federal level, as long as it is updated in its appellate microsystem.